Визначення раціональних параметрів пневмомеханічного висівного апарата з периферійним розташуванням комірок та інерційним видаленням зайвого насіння - Васильковська, К. В.; Васильковская, К. В.; Vasylkovska, K. (ЦНТУ, 2019)
В статті запропоновано нову конструкцію пневмомеханічного висівного апарата з периферійним розташуванням комірок на висівному диску та пасивним пристроєм, що дозволяє видаляти зайве насіння інерційним способом та забезпечити точний висів насіння просапних культур. Проведена серія досліджень запропонованого висівного апарата для насіння цукрових буряків дозволила визначити вплив розрідження у вакуумній камері висівного апарата та колової швидкості комірок на коефіцієнт заповнення комірок. Запропонована конструкція нового пневмомеханічного висівного апарата дозволяє значним чином знизити вакуум в системі, при цьому збільшується колова швидкість комірок висівного диска до значень поступальної швидкості посівного агрегату, що забезпечує сталу точку скидання насіння з висівного диска та однакові траєкторії їх польоту до борозни при якісному заповненні комірок. Для досягнення поставлених задач з визначення раціональних параметрів та режимів роботи висівного апарата використовувався метод планування багатофакторного експерименту. При цьому були визначені основні рівні та інтервали варіювання факторів для висіву насіння цукрових буряків при визначенні коефіцієнта заповнення комірок висівного диска. За допомогою пакету прикладних програм Statistica 6.0. для параметра оптимізації – коефіцієнта заповнення комірок побудовано поверхню відгуку та лінії рівного виходу. В статье предложено новую конструкцию пневмомеханического высевающего аппарата с перрифферийным распложением ячеек на высевающем диске и пассивным устройством, которое позволяет удалять лишниие семена инерционным способом и обезпечивает точный высев семян просапных культур. Проведенная сеиия исследованийпредложенного высевающего аппарата для семян сахарной свеклы позволила определить влияние разрежения в вакуумной камере высевающего аппарата и круговой скорости ячеек на коэфициент заполнения ячеек.Предложенная конструкция нового пневмомеханиченского высевающего аппарата позволяет значительным образом снизить вакуум в системе, при этом увеличивается круговая скорость ячеек высевного диска до значений поступальной скорости посевного агрегата,что обеспечивает постоянную точку сбрасывания семян с высеівного диска и одинаковые траектории их полета к борозне при качественном заполнении ячеек. Для достижения поставленных задач с определением рациональных параметров и режимов работы высевного аппарата использовался метод планирования многофакторного экспериментуа При этом были определены основные уровни и параметры варьирования факторов для висева семян сахарной свееклы при определении коэффициента заполнения ячеек высевного диска. С помощью пакета прикладных программ Statistica 6.0. для параметра оптимизации – коефициента заполнения ячеек построено повенрхность отклика и линии ровного выхода. Modern pneumatic sowing drill devices of high precision, despite a long history of their creation and improvement, have several disadvantages, the main ones are: insufficient dosing capacity caused by limited seed angular velocity of the disk (Vk ≤0,5 m/s) and the presence of uncontrolled redistribution random intervals between the seeds in the furrow, because of the high relative speed of the seed in contact with the latter during the drills movement with nominal speeds (Vc = 1,5...2,5 m/s). Eliminating these deficiencies is achieved by increasing the angular velocity of the sowing disk and its harmonization with the drills travelling speed. In the article we provide the new design of pneumatic sowing machine with peripheral cells on the seed disk and a passive device for removing extra seeds with inertia method for precise seeding of cultivated crops. A series of studies was proposed for sugar beet seeds sowing device, we defined the influence of dilution in a vacuum chamber of sowing device and angular velocity cell seed disk on the cells filling factor. The design of the new pneumatic sowing machine can significantly reduce the vacuum in the system having increased the angular speed in cell seed disk to the values of seeding device travelling speed, thus provide a constant point of seeds drop from the seed disc at the same trajectory of their flight to the furrows and the qualitative cells filling. To determine the rational parameters and modes of sowing device we used method of multifactor experiment planning. We determined the main levels and intervals of varying factors for sugar beet sowing along with determining the filling factor of cell seed disk. With application of package Statistica 6.0. for parameter optimization - cell seed disk filling factor was constructed response surface and line of even output. Thus, the design of the investigated pneumomechanical apparatus will allow to increase the circular velocity of the cells and reduce their number on the seeding disk, and to a considerable extent reduce the vacuum in the vacuum chamber. The proposed pneumomechanical seeding machine allows to increase the processability of sowing seeds of sown crops and reduce its energy intensity.
Определение рациональных параметров пневмомеханического высевающего аппарата с перрифферийным распложением ячеек и инерционным выдалением лишних семян
Determination of Rational Parameters Pneumomechanical Seeding Machine with Peripheral Arrangement of the Cell and Inertial Edition of Extra Seeds
Keywords: пневмомеханічний висівний апарат; висівний диск; експеримент; коефіцієнт заповнення комірок; розрідження; колова швидкість комірок; пневмомеханический высевающий аппарат; высевающий диск; эксперимент; коэфициент заполнения ячеек; разрежение; круговая скорость коморок